2009
DOI: 10.1186/1749-799x-4-41
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic lateral ankle instability: a modified broström technique using three suture anchors

Abstract: Ankle sprains are very common injuries seen in the athletic and young population. Majority of patients will improve with a course of rest and physical therapy. However, with conservative management about twenty percent of all patients will go on to develop chronic lateral ankle instability. This manuscript describes our detailed surgical technique of a modification to the original Broström procedure using three suture anchors to anatomically reconstruct the lateral ankle ligaments to treat high demand patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
(15 reference statements)
0
19
0
2
Order By: Relevance
“…23 Many surgeons have adapted the procedure to include the use of suture anchors with good results. 20,22,25 Our data suggested that none of the anchors pulled out of bone during testing. Thus, we are not able to comment on pull-out strength in this study because the mode of failure was always at the tissue level.…”
Section: Discussionmentioning
confidence: 93%
“…23 Many surgeons have adapted the procedure to include the use of suture anchors with good results. 20,22,25 Our data suggested that none of the anchors pulled out of bone during testing. Thus, we are not able to comment on pull-out strength in this study because the mode of failure was always at the tissue level.…”
Section: Discussionmentioning
confidence: 93%
“…Surgery is recommended in patients with chronic lateral ankle instability resistant to conservative methods, so as to restore stability, prevent intra-articular derangement and avoid early osteoarthritis [1,8,9,15,17]. The Broström technique, possibly associated with the Gould modification, is the gold standard of all proposed surgical repair techniques for chronic lateral ankle instability [1,12,31,32]. It requires that the ligament remnant should not be too weak, damaged or too scarred to allow a stable good quality repair.…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques including the use of suture anchors, part of the peroneus brevis tendon, or a distal fibula periosteal flap have been described. 12,13,23,25 The periosteal flap augmentation technique has since been used by several other authors with good outcomes. 3,7,8,[24][25][26] The purported benefits include the use of a small incision, avoidance of a foreign implant with its attendant risks and costs, and preservation of local tendons.…”
Section: Discussionmentioning
confidence: 99%